Language Awareness as a Catalyst for Modern Language Learning: Italian in Canadian Post-secondary Education - Barysevich, Alena; Smeets, Liz (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2025)
This paper investigates the integration of a language awareness approach within Canadian post-secondary education, with a focus on Italian as an Additional Language (IAL). Drawing on student and instructor surveys and self-assessment data collected between 2020 and 2024, the study illustrates how linguistic training can be embedded into the core curriculum of introductory IAL courses through targeted activities that promote language awareness. This pedagogical intervention was developed in response to challenges experienced by students when transitioning from high school to university. We introduced language-awareness exercises to address substantial gaps in foundational linguistic knowledge among students and language instructors. We offered linguistically enriched activities that support IAL learners in reactivating prior language knowledge and in transferring key linguistic principles across languages. This process fosters a more analytical and critical orientation toward language learning. The study furthermore discusses how these activities inform broader instructional practices and contribute to a more effective pedagogical design within post-secondary IAL programs.